The Effect of Training and Motivation on Employee Performance in the Finance, Accounting & Tax Division - Komara, Acep; Harsono, Yhonanda; Wihayati, Welly; Rahayu, Ngesti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the effect of training on the performance of employees in the Finance, Accounting & Tax division. The population and sample of this study were 39 people. The variables in this study consisted of training (X1) and Motivation (X2) and Employee Performance (Y). Methods of collecting data using observation and questionnaires. Data analysis methods used are Multiple Linear Regression Analysis, Multiple Correlation Coefficient Analysis (R), Determination Coefficient Analysis, Hypotensic Test (T-test, and test f). The results showed that there was a positive and significant influence or relationship between Training and Motivation on Employee Performance with the value of the Correlation Coefficient of 0.510, meaning that training and motivation variables had a relationship with moderate correlation with employee performance. Obtained training t value (X1) is (2.837 > 2,028), meaning that there is a positive and significant. While the value of t count motivation (X2) is (2,340> 2,028), it can be said to be significant. This means there is a positive and significant influence between motivation on employee performance. The value of F count> F table or (6.344> 3.26). This meaning there is a significant effect simultaneously between training and motivation variables on employee performance.